Does Imitation Facilitate Word Recognition in a Non-Native Regional Accent? - Nguyen, Noel; Dufour, Sophie; Brunellière, Angèle (Frontiers in Psychology, 2012)
We asked to what extent phonetic convergence across speakers may facilitate later word recognition. Northern-French participants showed both a clear phonetic convergence effect towards Southern French in a word-repetition task, and a bias towards the phonemic system of their own variety in the recognition of single words. Perceptual adaptation to a non-native accent may be difficult when the native accent has a phonemic contrast that is associated with a single phonemic category in the non-native accent. Convergence towards a speaker of a non-native accent in production may not prevent each speaker's native variety to prevail in word identification. Imitation has been found in previous studies to contribute to predicting upcoming words in sentences in adverse listening conditions, but may play a more limited role in the recognition of single words.